IDENTIFIKASI PERCEPATAN TANAH MAKSIMUM DI WILAYAH BENGKULU DENGAN METODE KAWASHUMI - Reni Nurjannah; Mulkan Iskandar; Lailatul Husna Lubis (Universitas Riau, 2023)
Maximum soil acceleration is the greatest value of increasing soil acceleration caused by a specified period of time. Maximum ground acceleration is very important to do, to reduce the risk due to an earthquake that occurs. This research is expected to be able to determine the value of the largest increase in ground velocity and areas that have the greatest level of possible danger due to ground acceleration using the Kawashumi method. From the after effects of the investigation that has been finished, it is obtained that the maximum ground acceleration value is 661.7182528 gal and it can be seen that Muko-Muko Regency in the Bengkulu region has a risk due to high ground acceleration.